Less Conserved LRRs Is Important for BRI1 Folding - Hou, Qiang; Saima, Shehzadi; Ren, Hong; Ali, Khawar; Bai, Chengke; Wu, Guang; Li, Guishuang (Frontiers in Plant Science, 2019)
Brassinosteroid insensitive 1 (BRI1) is a multidomain plant leucine-rich repeat receptor-like kinase (LRR-RLK), belongs to the LRR X subfamily. BRI1 perceives plant hormone brassinosteroids (BRs) through its extracellular domain that constitutes of LRRs interrupted by a 70 amino acid residue island domain (ID), which activates the kinase domain (KD) in its intracellular domain to trigger BR response. Thus, the KD and the ID of BRI1 are highly conserved and greatly contribute to BR functions. In fact, most bri1 mutants are clustered in or surrounded around the ID and the KD. However, the role of the less conserved LRR domains, particularly the first few LRRs after the signal peptide, is elusive. Here, we report the identification of a loss-of-function mutant bri1-235 that carries a mutation in the less conserved fourth LRR of BRI1 extracellular domain in Arabidopsis. This mutant had a base alteration from C to T, resulting in an amino acid substitution from serine to phenylalanine at the 156th position of BRI1. Compared with the wild-type plants, bri1-235 exhibited round leaves, prolonged life span, shorter stature, and approximately normal fertility under light conditions. The bri1-235 mutant was less sensitive to exogenous brassinolide under normal conditions. Importantly, both wild-type BRI1 expression and a sbi1 mutant that activates BRI1 rescued bri1-235 and resembled the wild type. Furthermore, bri1-235 protein was localized in endoplasmic reticulum rather than plasma membrane, suggestive of a cause for reducing BR sensitive in bri1-235. Taken together, our findings provide an insight into the role of the less conserved LRRs of BRI1, shedding light on the role of LRRs in a variety of LRR-RLKs that control numerous processes of plant growth, development, and stress response.